Identification of new immune subtypes of renal injury associated with anti-neutrophil cytoplasmic antibody–associated vasculitis based on integrated bioinformatics analysis - Lin, Lizhen; Ye, Keng; Chen, Fengbin; Xie, Jingzhi; Chen, Zhimin; Xu, Yanfang (Frontiers in Genetics, 2023)
Anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is a systemic autoimmune disease that may lead to end-stage renal disease. However, few specific biomarkers are available for AAV-related renal injury. The aim of this study was to identify important biomarkers and explore new immune subtypes of AAV-related renal injury. In this study, messenger RNA expression profiles of AAV and AAV-related renal injury were downloaded from the Gene Expression Omnibus (GEO) database. Weighted gene co-expression network analysis (WGCNA) was performed to identify the module genes most related to AAV. The key module genes of WGCNA were then intersected with the AAV- and nephropathy-related genes in the Genecards database to identify key genes of AAV-related renal injury. Eight co-key genes (AGTR2, ANPTL2, BDKRB1, CSF2, FGA, IL1RAPL2, PCDH11Y, and PGR) were identified, and validated the expression levels independent datasets. Receiver operating characteristic curve analysis revealed that these eight genes have major diagnostic value as potential biomarkers of AAV-related renal injury. Through our comprehensive gene enrichment analyses, we found that they are associated with immune-related pathways. In addition, non-negative matrix factorization clustering of co-key genes was performed to identify potential injury subtypes of AAV-related renal injury. A correlation analysis with prognostic data from the Nephroseq database indicated that the expression of co-key genes was positively co-related with the glomerular filtration rate. In conclusion, we identified 8 valuable biomarkers that firmly correlate with the diagnosis and prognosis of AAV-related renal injury. These markers may help identify new immune subtypes for AAV-related renal injury.